GOVERNANCE OF PASSPORT ISSUANCE SERVICES DURING THE COVID-19 PANDEMIC: A CASE STUDY AT THE IMMIGRATION OFFICE CLASS I CHECKPOINT YOGYAKARTA - Fitriyono, Junaidul -; Puspita, Intan Sari; Yuni, Farikah; Marthalia, Virgin (Jurnal Ilmiah Kajian Keimigrasian, 2023)
Passport issuance at the Yogyakarta Class I Checkpoint Immigration Office during the COVID-19 pandemic experienced various fluctuations. At the beginning of the pandemic, it experienced a very significant decline with a closure then continued with restrictions until the implementation of the new normal. The response made by the Yogyakarta Class I Checkpoint Immigration Office by implementing innovations derived from the Directorate General of Immigration’s policies in the form of the M-Passport application and the Eazy Passport program, as well as internally created innovations such as Karyo Sepakat, Bilang Karyo and Mas Karyo is enough to encourage an increase in passport applications. Networking in order to increase passport applications is also carried out with the Eazy Passport program and cooperation with institutions including in education, business and government sectors. The establishment of UKK at the UGM International Office, ULP at Lippo Plaza Mall and MPP in Wates Kulon Progo are part of network development in expanding passport issuance services outside the Yogyakarta Class I Checkpoint Immigration Office. System development and socialization are important factors in order to maintain the sustainability of innovation and efforts to maintain the networking that has been established.